Sodium Selenite Attenuates Balloon Injury-Induced and Monocrotaline-Induced Vascular Remodeling in Rats - Cai, Changhong; Wu, Yonghui; Yang, Lebing; Xiang, Yijia; Zhu, Ning; Zhao, Huan; Hu, Wuming; Lv, Lingchun; Zeng, Chunlai (Frontiers in Pharmacology, 2021)
Vascular remodeling (VR), induced by the massive proliferation and reduced apoptosis of vascular smooth muscle cells (VSMCs), is primarily responsible for many cardiovascular conditions, such as restenosis and pulmonary arterial hypertension. Sodium selenite (SSE) is an inorganic selenium, which can block proliferation and stimulate apoptosis of tumor cells; still, its protective effects on VR remains unknown. In this study, we established rat models with carotid artery balloon injury and monocrotaline induced pulmonary arterial hypertension and administered them SSE (0.25, 0.5, or 1 mg/kg/day) orally by feeding tube for 14 consecutive days. We found that SSE treatment greatly ameliorated the development of VR as evidenced by an improvement of its characteristic features, including elevation of the ratio of carotid artery intimal area to medial area, right ventricular hypertrophy, pulmonary arterial wall hypertrophy and right ventricular systolic pressure. Furthermore, PCNA and TUNEL staining of the arteries showed that SSE suppressed proliferation and enhanced apoptosis of VSMCs in both models. Compared with the untreated VR rats, lower expression of PCNA and CyclinD1, but higher levels of Cleaved Caspase‑3 and Bax/Bcl‑2 were observed in the SSE-treated rats. Moreover, the increased protein expression of MMP2, MMP9, and activation of the AKT/GSK3β/β-catenin pathway that occurred in the VR rats were significantly inhibited by SSE. Collectively, treatment with SSE remarkably attenuates the pathogenesis of VR, and this protection may be associated with the inhibition of AKT signaling and prevention of VSMC’s dysfunction. Our study suggest that SSE is a potential agent for treatment of VR-related diseases.